Resettlement Programme for Landless Agricultural Labourers - Planning Commission (Planning Commission, 1968)
Agricultural development and rural reconstruction has been the corner-stone of Development Planning. Series of land reform measures releasing surplus lands above ceiling, reclamation of culturable waste lands, Bhoodan and Gramdan movement have been the various measures through which programme of land settlements have been effected for the benefit of backward sections of the community specially the landless agricultural labourers. Resettlement programmes which had been undertaken during all the Plans, received pointed emphasis with the Centrally Sponsored schemes initiated during the Third Plan.
Case Studies of Selected Colonies Programme Evaluation Organisation Planning Commission Govt. of India